Impact of justice in the supply chain relationship on implementing supply chain integration - Kim, Minkyun; Chai, Sangmi (International Journal of Supply Chain Management, 2019)
This research investigates the impact of procedural, distributive, and interactional justice in supplier relationships on implementing supply chain integration. This paper attempts to explain how justice in a supply chain relationship, relationship commitment to suppliers, and supply chain socialization affect a firm’s intention to implement supply chain integration. After collecting 254 survey responses from supply and purchasing managers in the manufacturing industry, data analysis is conducted using the partial least squares technique. Our research results indicate that relationship commitment to suppliers and supply chain socialization have a positive impact on justice in a supply chain relationship. Justice in a supply chain relationship and relationship commitment to suppliers positively affect intention to implement supply chain integration; however, supply chain socialization does not have a significant relationship with intention to implement supply chain integration. In addition, intention to implement supply chain integration leads to the actual behavior of implementing supply chain integration. Our research provides significant contributions to academia and industry by filling a gap in the literature and by offering meaningful insights for managers on the impact of justice in the supply chain and implementation of supply chain integration.